Shunt tube placement for amelioration of cerebrospinal fluid flow obstruction caused by spinal cord subarachnoid fibrosis in dogs. Issue 2 (February 2017) - Meren, Ilyssa L.; Chavera, Jessica A.; Alcott, Cody J.; Barker, Andrew K.; Jeffery, Nick D.
Abstract: Objective: To describe a novel technique for ameliorating cerebrospinal fluid flow obstruction secondary to pia‐arachnoid fibrosis in dogs and report outcome. Study Design: Descriptive report and retrospective case series. Animals: Dogs with cerebrospinal fluid (CSF) flow obstruction (n = 7). Methods: Medical records were searched for dogs that had a subarachnoid‐subarachnoid shunt placed for treatment of CSF flow obstruction. Data collected included age, sex, breed, clinical signs and duration of signs prior to examination, neurologic status and localization prior to surgery, pre‐surgical diagnostics, surgical technique, histopathology, postoperative neurologic examination, time to discharge from hospital, and outcome. Results: All dogs were diagnosed at surgery with a fibrotic adhesion between the arachnoid and pia mater. A subarachnoid shunting tube was implanted to allow CSF flow across the lesion site. Five dogs showed improvement of clinical signs, 3 of which showed complete recovery and 2 of which showed improvement without resolution of all clinical signs. Two dogs showed no change at 7 and 24 months postoperatively. Conclusion: Bridging a region of pia‐arachnoid fibrosis with a tube placed in the subarachnoid space can ameliorate or prevent progression of associated clinical signs.